Native American and Non-Native American Women Prisoners, Adverse Childhood Experiences, and the Perpetration of Physical Violence in Adult Intimate Relationships. - Jones, Melissa S.; Worthen, Meredith G. F.; Sharp, Susan F.; McLeod, David A. (Journal of Interpersonal Violence, 2021)
Native American women are at an especially high risk of lifetime violence, including childhood abuse, intimate partner violence (IPV), and sexual assault, and are overrepresented in the criminal justice system. Yet few studies have examined how the long-term effects of child maltreatment and other adverse childhood experiences (ACEs) affect Native American women prisoners' perpetration of physical violence in adult intimate relationships. This is surprising because ample research illustrates that childhood adverse events, particularly childhood abuse and neglect, have far-reaching effects across the life course and that these experiences are especially apparent in the lives of women involved in the criminal justice system. Using data from a stratified random sample of Native American (n = 92) and non-Native American (n = 264) women prisoners in Oklahoma, we explore the relationships between individual, cumulative, and clusters of ACEs as they relate to the use of physical violence in adult intimate relationships. Utilizing a feminist life course theoretical framework, our findings indicate that ACEs are not only critical to understanding adult IPV but also that the mechanisms and processes underlying the relationships between ACEs and the perpetration of physical violence in adult intimate relationships differ for Native American and non-Native American women. The findings of the current study demonstrate that it is imperative that prison programming includes trauma-informed and trauma-specific interventions targeting Native Americans.